Invasive Ductal Carcinoma Arising within a Fibroadenoma: A Case Report and Literature Review. - Pilika, Kliti; Shpuza, Aldo; Pilika, Anita; Xhetani, Xhesika (International Journal of Medical Science and Dental Health, 2024)
Background: Invasive ductal carcinoma (IDC) is the most common form of breast cancer, frequently presenting independently. Rarely, IDC arises within a fibroadenoma, a benign breast tumor typically associated with younger women. This case report and literature review aim to highlight the diagnostic challenges and clinical implications of finding IDC within a fibroadenoma. Case Presentation: A 36-year-old female patient presented with a dolent palpable mass in the right breast. Initial mammography described normal fibroglandular structures without significant findings. However, subsequent imaging ultrasound identified an 18x14 mm oval formation at the 9 o'clock position in the right breast, categorized as BI-RADS 3. Further histopathological evaluation after a biopsy confirmed the presence of a fibroadenoma with invasive ductal carcinoma, classified as Grade III with perivascular and neural infiltration. Discussion: The coexistence of IDC within a fibroadenoma poses significant diagnostic challenges due to the benign appearance of fibroadenomas on standard imaging modalities. This case emphasizes the need for a thorough evaluation and possible biopsy of fibroadenomas that exhibit atypical features or changes over time. Conclusion: This report underscores the importance of vigilance and comprehensive diagnostic strategies in cases of fibroadenomas, especially in patients with unusual or evolving lesions. The review of literature confirms that although rare, the occurrence of IDC within fibroadenomas can have significant implications for treatment and prognosis.